2008
DOI: 10.2459/jcm.0b013e3282f194f0
|View full text |Cite
|
Sign up to set email alerts
|

How many patients would be misclassified using M-mode and two-dimensional estimates of left atrial size instead of left atrial volume? A three-dimensional echocardiographic study

Abstract: Left atrial diameters and area measurements were poor predictors of 3D LAV, especially in the enlarged left atria. Therefore, these parameters can be misleading in assessing the severity of left atrial dilatation. Two-dimensional LAVs are accurate in estimating 3D LAV. The small additional accuracy obtained by using the biplane instead of the single-plane area-length method, and the fact that the biplane method is more technically demanding and time consuming, may allow the use of the area-length for routine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Sievers et al [42] compared, in a group of 15 healthy subjects, the biplane area-length method with real volume, showing that the biplane area-length method caused a significant overestimation. An echocardiographic study by Badano et al [43] that sought to assess how many patients would be misclassified using M-mode or 2D estimates of LA size instead of real LA volume, showed that both 1D and 2D parameters were poor predictors of LA volume, especially in enlarged atria. Like the single plane area-length method, the prolate-ellipsoid method assumes an ellipsoid geometry for the LA but systematically calculates smaller volumes than the biplane methods, which stems from any error with the section of the 3 pairs of coordinates creating a large difference in the volume measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Sievers et al [42] compared, in a group of 15 healthy subjects, the biplane area-length method with real volume, showing that the biplane area-length method caused a significant overestimation. An echocardiographic study by Badano et al [43] that sought to assess how many patients would be misclassified using M-mode or 2D estimates of LA size instead of real LA volume, showed that both 1D and 2D parameters were poor predictors of LA volume, especially in enlarged atria. Like the single plane area-length method, the prolate-ellipsoid method assumes an ellipsoid geometry for the LA but systematically calculates smaller volumes than the biplane methods, which stems from any error with the section of the 3 pairs of coordinates creating a large difference in the volume measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in contrast to the 2DE classi- Table 1. The prognostic value of LAV as a predictor of morbidity and mortality is well established in multiple disease states (14 -21) and is of particular importance in the context of the evaluation of LV diastolic function (1,6,13,22). However, the 2DE techniques routinely used in clinical practice to measure LAV are prone to errors because of their 2-dimensional nature.…”
Section: Impact Of Imaging Modality On the Classification Of LVmentioning
confidence: 98%
“…Not surprisingly, several studies have shown that 2DE underestimates LAV compared with imaging techniques that are free of these limitations, such as cardiac computed tomography (3,4) and cardiac magnetic resonance (CMR) (5). Importantly, this underestimation may contribute to misclassification of patients with LV diastolic dysfunction (6). Because real-time 3-dimensional echocardiography (3DE), the natural extension of 2DE, can overcome these limitations by allowing direct detection of LA boundaries in 3-dimensional space, it is attractive as a potentially more accurate and more reproducible alternative for the LAV measurements (7)(8)(9).…”
mentioning
confidence: 95%
“…However, given that MDCT echocardiographic views resulted in much closer size estimates and better correlation than did 2D TTE views, error due to geometric assumptions probably is not the major contributor to error. Results of studies [19][20][21] have suggested the use of real-time 3D TTE for chamber quantification may overcome the errors in 2D estimates of volume based on geometric assumptions. However, as shown by the significantly improved agreement with left atrial volume observed with use of the same geometric assumption on MDCT echocardiographic views, the error of estimation with TTE is related to poor subendocardial definition or foreshortening.…”
Section: Koka Et Almentioning
confidence: 99%